Effect of Salt and Garlic on the Quality and Microbial Content of Smoked Catfish (Pangasianodon hypophthalmus) - Begum, Mohajira; Akter, Tanjina; Minar, Maruf Hossain (International Journal of Bio-resource and Stress Management, 2023)
The purpose of this research was to determine quality and microbial content of smoked catfish (Pangasianodon hypophthalmus) using salt and garlic in two treatments—T1 (10% salt) and T2 (10% salt and 10% garlic). Smoked catfish samples subjected to bio-chemical and microbiological analysis were observed by changes in moisture, protein, fat, ash, total volatile nitrogen (TVN) value, total viable count (TVC), and total coliform, E. coli and Salmonella. Protein, fat, ash, TVN percentage of T2 was 53.71±0.35, 17.67±0.40, 7.87±0.13 and 7.57±0.13, respectively which was higher than T1 (48.65±0.67, 14.39±0.62, 7.56±0.92 and 6.47±0.65, respectively). Besides, moisture percentage and TVC of T2 (24.59±0.82 and 50 cfu g-1) was lower than T1 (42.91±1.02 and 60 cfu g-1). Total coliform, E. coli was <3 MPN g-1 and Salmonella was absent in both the treatments. As a result , moisture and fat content shows inverse relationship which is similar to T2 and was the best